Hišni obisk - Kersnik, Janko (Medicinski razgledi, 1996)
House calls are presented as an integral part of the general practitioner's daily work. Various forms of house calls, as well as their frequency, financing and the associated problems are discussed.
Keywords: medicina; medicine; zdravljenje na domu; obiski